International Accounting Standards and Accounting Quality - BARTH, MARY E.; LANDSMAN, WAYNE R.; LANG, MARK H. (Journal of Accounting Research, 2008)
ABSTRACT We examine whether application of International Accounting Standards (IAS) is associated with higher accounting quality. The application of IAS reflects combined effects of features of the financial reporting system, including standards, their interpretation, enforcement, and litigation. We find that firms applying IAS from 21 countries generally evidence less earnings management, more timely loss recognition, and more value relevance of accounting amounts than do matched sample firms applying non‐U.S. domestic standards. Differences in accounting quality between the two groups of firms in the period before the IAS firms adopt IAS do not account for the postadoption differences. Firms applying IAS generally evidence an improvement in accounting quality between the pre‐ and postadoption periods. Although we cannot be sure our findings are attributable to the change in the financial reporting system rather than to changes in firms' incentives and the economic environment, we include research design features to mitigate effects of both.